HAKIKAT PENYULUHAN PEMBANGUNAN DALAM MASYARAKAT - Dwi Siswanto (Jurnal Filsafat "WISDOM", 2012)
The essence of development education can be obtained by explaining its meaning; explaining and analyzing its functions and principles in the community; and describing its essential elements. Based on the study that have been conducted, the essence of development education can be described as follows. First, development education is a process of information dissemination; process of explanation; process of behavioral change; the educational process; and social-engineering process. Second, its functions is to change people's behavior better to improve the quality of life. Third, its principles include: the interests and needs; grassroots organizations; culture changes; cooperation and participatory democracy in the application of science; learning by doing; the use of appropriate methods; leadership; trained specialists; education must consider the family as a social unit; education should be able to realize satisfaction. Fourth, the elements in development education are extension, objectives, methods, media, place and time.